Fire behaviour of protected W-S-W connections with a steel plate as the central member and different dowels diameter - Martins, Rúben D A R (2019)
The main objective of this work is to present wood-steel-wood (W-S-W) connections in double-shear, joined by steel dowel fasteners and a steel plate as the central member. For each studied connection, different dowel diameters and external applied tensile loads in fire situation shall be taken in account. Considering the rules presented in Eurocode 5, part 1-1 and 1-2, the calculated number of dowels will be arranged in lines and columns and carry out an imposed spacing between the connectors. This work is intended to study the W-S-W connection exposed to fire using the standard curve ISO834. In the wood plates will be used a glue laminated wood, as yellow birch, with characteristics equals to GL28H. For protected connections three types of gypsum will be used in order to obtain a better insulation. Simplified equations from Eurocode 5, part 1-1 and 1-2, will be used to verify the behaviour of the connections at high temperature. A numerical procedure based on finite element method was also implemented to produce simulations focused on thermal analysis. The comparison of several results between analytical and numerical calculations showed a favourable accordance. The numerical model permits verify the effect of the steel dowels, steel plate and gypsum in the wood charring rate evolution. Even though the connection can resist for thirty minutes, is possible to observe the char layer both on protected and unprotected connection being the last the most affected.